Controlled layer-by-layer assembly and structured coloration of Ti3C2Tz MXene/polyelectrolyte heterostructures - Natalie N. Neal; Kailash Arole; Huaixuan Cao; Vrushali Kotasthane; Sisi Xiang; Diego Ross; Peter R. Stevenson; Miladin Radovic; Micah J. Green; Jodie L. Lutkenhaus (npj 2D Materials and Applications)
Abstract Structural color arises from light scattering rather than organic pigments and can be found in Nature, such as in bird feathers and butterfly wings. Synthetic materials can mimic Nature by leveraging materials with contrasting optical characteristics by controlling each materials’ spatial arrangement in a heterostructure. Two-dimensional MXene nanosheets are particularly interesting due to their unique optical properties, but MXenes have not been used directly as a structural colorant because it is challenging to control the spatial placement of MXenes at the nanometer level. Here, we report the emergence of structural color in layer-by-layer (LbL) assemblies of Ti3C2Tz MXene nanosheets and polyelectrolyte heterostructures with controlled block thicknesses. The block thickness and spatial placement of MXene are controlled by the assembly’s salt concentration and number of layer pairs. This work demonstrates that optical characteristics of MXene/polyelectrolyte heterostructures depend on MXene content and placement, while deepening the understanding of MXenes within structural color films.